Efficient hydrodeoxygenation of tetrahydrofuran 2,5-dicarboxylic acid to adipic acid over Pt-MOx catalysts: an experimental and computational study (2024)
The production of adipic acid (AA) from the ring-opening hydrogenolysis (hydrodeoxygenation - HDO) of tetrahydrofuran 2,5-dicarboxylic acid (THFDCA) by metal-metal oxide catalysts (Pt-MOx/TiO2 and Pt/MOx) was evaluated. Correlations between AA yield, or products distribution, and the type of active centers in the catalyst surface were established by studying the type (MOx: WOx, MoOx, and ZrOx), the amount of metal oxide (MOx:Pt molar ratio), and the reaction temperature (180ºC, 220ºC, and 240ºC) in Pt-MOx/TiO2 and Pt/MOx. The activity results show that only the catalysts that contain both Pt and Mo produced AA at 220ºC, with yields of 24 % for Pt-MoOx/TiO2 (4 wt % Pt, 1:1 Mo:Pt molar ratio) and 34% for 4 wt % Pt/MoO3. At 180ºC, these catalysts exhibited high selectivity towards reducing the carboxyl group. Computational studies using DFT suggest that this behavior is due to the preferential interaction between the oxygen vacancy (O-VAC) in MoO3 and the Cdouble bondO bond in the carboxyl group in 2-hydroxyadipic acid (2-HAA), the first observed intermediate from the HDO of THFDCA. Coverage of this adsorption configuration decreases at temperatures above 200ºC, where the interaction between the alcohol group in the 2 C position in 2-HAA and the Brønsted acid site (BAS) on the surface of MoO3 is preferred. This latter interaction could promote the acid-catalyzed dehydration of the alcohol group to obtain AA. Increasing the amount of Mo to 5:1 Mo:Pt in Pt-MoOx/TiO2 and decreasing the Pt content to 0.1 wt % in Pt/MoO3 decreases the selectivity to alcohols, increasing the AA yield to 55 % at 220ºC and 65 % at 240ºC for both catalysts. This enhancement in performance is consistent with the findings from the DFT studies. To our knowledge, this is the highest yield reported for AA production from THFDCA or FDCA by metal-metal oxide catalysts.